PEREIRA, R. H. S. (2012). Averróis ”“ A Arte de Governar. São Paulo, Editora Perspectiva. 335 p. - Nascimento, Carlos Arthur Ribeiro do (Revista Archai, 2013)
PEREIRA, R. H. S. (2012). AVERRÓIS ”“ A ARTE DE GOVERNAR. SÃO PAULO, EDITORA PERSPECTIVA. 335 P.